Pengaruh Implementasi Model Pembelajaran Quantum Teaching dalam Pembelajaran PPKn Terhadap Hasil Belajar Aspek Kognitif, Afektif, dan Psikomotor Siswa Kelas V SDN Muara Rengas - Suyamto; Puspa Djuwita; Endang Widi Winarni (UNIB Press, 2024)
This study aims to determine the influence of the Quantum teaching model on the learning outcomes of cognitive, affective, and psychomotor aspects of students in PPKn learning on Socio-Cultural Diversity material. The sample in the study was 43 students of Class VA (experimental class) and VB (control class). The method used in this study is quasi-experimental research. The research instrument uses a written test, attitude scale questionnaire, and practice/performance assessment rubric. The results of this study show that: 1) there is an influence of the implementation of the quantum teaching learning model in PPKn Learning on the learning outcomes of cognitive aspects of fifth grade students, 2) there is an influence of the implementation of the quantum teaching learning model in PPKn learning on the learning outcomes of affective aspects of fifth grade students, 3) there is an influence of the implementation of the quantum teaching learning model in PPKn learning on the learning outcomes of psychomotor aspects of fifth grade students. The implementation of the quantum teaching model can affect the learning outcomes of cognitive, affective, and psychomotor aspects in PPKn learning.